The use of ring-porous East Asian ash (Fraxinus japonica (Thunb.) Steud.) and oak (Quercus spp.) cross-sections as eco-friendly resonance-absorbing materials for building. Issue 6 (2nd November 2022) - Jang, Eun-Suk; Kang, Chun-Won
ABSTRACT: We examined the suitability of East Asian ash ( Fraxinus japonica (Thunb.) Steud. ) and oak ( Quercus spp. ) cross-sections as potential eco-friendly sound-absorbing materials for building. We examined the macroscopic anatomical structure of the woods and determined their gas permeability, pore size, and porosity. We also measured the sound absorption coefficient of each material using an impedance tube. In the absence of an air back cavity, both species failed to meet the sound absorption standards required by ISO 11654. However, in the presence of an air back cavity, resonance absorption peaked at a low frequency, corresponding to ISO 11654 class D performance. In sum, these ring-porous woods can be useful as eco-friendly, resonance-sound-absorbing materials.